The Relationship between Community Social Capital and Rural Tourism Innovation in Indonesia - Wafa, Rizki Hanifa Shohibul; Prayitno, Gunawan; Wicaksono, Agus Dwi; Rahmawati; Hayat, Ainul; Siankwilimba, Enock; Hiddlestone-Mumford, Jacqueline (Perencanaan Wilayah dan Kota FT UB, 2024)
As rural tourism becomes a popular trend today, innovation in tourism development is needed to be sustainable and maintain the community's cultural values. Social capital is the basic capital of society for building networks and working together to achieve goals. Therefore, this research examines how social capital can contribute to tourism development innovation. The questionnaire as a research instrument was aimed at 248 families, and the results were analyzed using SmartPLS 3.0-type SEM software. The research results show that social capital originating from trust, norms, and community networks significantly affects innovation in Ponggok Village. This capital can accelerate the growth of innovation in village development. Village governments can provide discussion forums related to tourism, thereby enabling community involvement. Existing innovations must be maintained and optimized to create a competitive tourist village. Village governments must also focus on improving existing tourism services and fostering new ideas from the community.